Determinants of Purchase Intention on Green Smartphone - Humairoh Humairoh; Mohammad Annas; Hening Chintia Fratiwi (Asian Journal of Management, Entrepreneurship and Social Science, 2023)
The motive of this study became to decide and examine the credibility of green brands, private label products and electronic word of mouth on the purchase intention of iPhone smartphones each partly and concurrently. The sample consisted of 140 respondents from Universitas Muhammadiyah Tangerang college students. This studies approach makes use of quantitative. The sampling technique used was purposive sampling. The data collection method became achieved the use of a questionnaire device with a Likert Summated score (LSR) with the evaluation criteria strongly disagree - strongly agree. The effects showed that green brand credibility has a positive and significant effect on purchase intention of iPhone smartphones, private label products have a positive and significant impact on purchase intention of iPhone smartphones and E-WOM has a positive and significant impact on purchase intention of iPhone smartphones. Simultaneously green credibility, private label products and E-WOM have a positive and significant impact on purchase intention in iPhone smartphones. From the results of the regression equation shows that the have an impact on of electronic word mouth has the highest have an effect on then private label products and the smallest is green brand credibility. That these marketers to offer information on iphone products that iphone products have long past green spread that widely through electronic word of mouth that iphone smartphones are green brands.